CcpA forms complexes with CodY and RpoA in Bacillus subtilis - Wünsche, Andrea; Bartholomae, Maike; Hammer, Elke; Völker, Uwe; Seidel, Gerald; Burkovski, Andreas; Hillen, Wolfgang (Febs Journal, 2012)

Differential NtcA responsiveness to 2-oxoglutarate underlies the diversity of C/N balance regulation in Prochlorococcus - Dominguez-Martin, Maria A.; Lopez-Lozano, Antonio; Claveria-Gimeno, Rafael; Velazquez-Campoy, Adrian; Seidel, Gerald; Burkovski, Andreas; Diez, Jesus; Garcia-Fernandez, Jose M. (Frontiers in Microbiology, 2018)

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

Structural insight into operator dre-sites recognition and effector binding in the GntR/HutC transcription regulator NagR - Fillenberg, Simon; Grau, Florian; Seidel, Gerald; Muller, Yves (Nucleic Acids Research, 2015)
The uptake and metabolism of N-acetylglucosamine (GlcNAc) in Bacillus subtilis is controlled by NagR (formerly named YvoA), a member of the widely-occurring GntR/HutC family of transcription regulators. Upon binding to specific DNA operator sites (dre-sites) NagR blocks the transcription of genes for GlcNAc utilization and interaction of NagR with effectors abrogates gene repression. Here we report crystal structures of NagR in complex with operator DNA and in complex with the putative effector molecules glucosamine-6-phosphate (GlcN-6-P) and N-acetylglucosamine-6-phosphate (GlcNAc-6-P). A comparison of the distinct conformational states suggests that effectors are able to displace the NagR-DNA-binding domains (NagR-DBDs) by almost 70 Å upon binding. In addition, a high-resolution crystal structure of isolated NagR-DBDs in complex with palindromic double-stranded DNA (dsDNA) discloses both the determinants for highly sequence-specific operator dre-site recognition and for the unspecific binding of NagR to dsDNA. Extensive biochemical binding studies investigating the affinities of full-length NagR and isolated NagR-DBDs for either random DNA, dre-site-derived palindromic or naturally occurring non-palindromic dre-site sequences suggest that proper NagR function relies on an effector-induced fine-tuning of the DNA-binding affinities of NagR and not on a complete abrogation of its DNA binding.